Pengaruh Penundaan Pelaksanaan Pemilu Yang Melanggar Sistem Konstitusi Di Indonesia - Dinita Ardiyanti; Rayhan Nizam Mahendra; Febyola Alistya Senoaji; Nafiza Salsabila Faliha; Laga Sugiarto (Jurnal Hukum dan Sosial Politik, 2023)
Mr. Joko Widodo, The President of the Republic of Indonesia, has recently been inseparable from various hot issues that have been debated in the community during his tenure for two terms. In recent years, there have been discussions for postponing elections made by a range of political figures, and people who support the issue. The big impact caused by this discourse includes demonstrations and resistance from the community. The stability of a country is also affected by an increasingly tense political situation. The danger of democracy allowing its people's freedom to speak raises political turmoil, which can undermine the values of constitutional sovereignty and democracy. The article investigates Indonesia's laws governing the delay of national elections and the recommendations for the implementation of the discourse on postponing the general election against the sovereignty of the constitution and democracy as well as the consequences of its implementation. The study's methodology is normative juridical with a legislative and conceptual focus. Data were gathered through a literature review of secondary legal materials, such as the general election law, secondary sources in the form of journals and books, and tertiary sources in the form of articles from websites. The conclusion of the findings of this article in the form of a constitution does not regulate or require the prorogation of the general elected. However, to strive for the agenda, there is a method of forming a Government Regulation in Lieu of Law that involves a mismatch in the periodization of the position of state stakeholder described in the 1945 Constitution and is an indication of contraindications to constitutional sovereignty. Constitutional amendments are the second option that can pose a threat to the sustainability of electoral principles that are part of a form of democratic sovereignty.